Analysis of Image Messages on Cigarette Packs Using Religious, Persuasive, and Financial Messages on Smoking Behavior - Ajeng Anasti; Ayu Permata Sari; Chintya Andini; Dian Fransiska Ramadhani (Pena Cendekia Insani, 2021)
Smoking behavior is still a problem in the world and Indonesia. The policy of picture messages on cigarette packs is regulated in the Minister of Health Regulation No. 28 of 2013 concerning the Inclusion of Warnings and Health Information on Tobacco Product Packaging. The purpose of this study was to analyze the picture messages on cigarette packs using religious, persuasive, and financial messages on smoking behavior. This research is quantitative research with a cross-sectional study design with primary data. This research was conducted in Indonesia. The time of this research was in January-August 2021. The sample in this study was 430. The data collection technique in this study was using a questionnaire with an online google form. Data analysis in this study is Univariate analysis with descriptive. The results of the study are the impact of religious image messages on cigarette packs on smoking behavior, namely the average respondent feels afraid of 8.42, feels disgusted by 7.40. believe in the picture is 8.46, feel worried about 8.61, feel the picture is excessive 3.71, want to exchange the picture of a cigarette message with another one is 1.52 and want to stop smoking is 8.98. It is hoped that the Government will conduct a more effective campaign to message the dangers of cigarettes on cigarette packs to reduce the number of smokers in Indonesia and review or update the images on cigarette packs with more effective ones to be enlarged to reduce the number of smokers among Indonesia.